Model Konseling Islami Berbasis Kisah Nabiuntuk Penguatan Nilai Moral Anak Usia Dini - Zul Arwan (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to develop an Islamic counseling model based on the stories of the Prophets as an effort to strengthen moral values among early childhood students at TK Islam Al Amin, Medan Johor. The research employed a descriptive qualitative approach involving 20 children aged 5–6 years. The intervention was conducted over eight sessions within one month. Research instruments included a moral development observation sheet, teacher interview guidelines, and documentation of learning activities. The findings revealed a significant improvement in the children’s moral development, with the average moral score increasing from 63% to 87%. The most notable growth was observed in the aspects of honesty and empathy. These results were supported by teachers’ reports, which indicated that storytelling based on the lives of the Prophets was effective, as it provided concrete examples that were easy for children to understand and emulate. Based on these findings, the Islamic counseling model using the stories of the Prophets is recommended for continuous application in Islamic educational institutions to nurture children’s character from an early age